Imaging of hypoxia with 18F‐FAZA PET in patients with locally advanced non‐small cell lung cancer treated with definitive chemoradiotherapy. Issue 4 (14th June 2013) - Trinkaus, Mateya E; Blum, Rob; Rischin, Danny; Callahan, Jason; Bressel, Mathias; Segard, Tatiana; Roselt, Peter; Eu, Peter; Binns, David; MacManus, Michael P; Ball, David; Hicks, Rodney J
Abstract Introduction For many cancers, tumour hypoxia is an adverse prognostic factor, and increases chemoradiation resistance; its importance in non‐small cell lung cancer (NSCLC) is unproven. This study evaluated tumoural hypoxia using fluoroazomycin arabinoside (18F‐FAZA) positron emission tomography (PET) scans among patients with locoregionally advanced NSCLC treated with definitive chemoradiation. Methods Patients with stage IIIA‐IIIB NSCLC underwent 18F‐FAZA PET scans and 18F‐2‐deoxyglucose (FDG)‐PET scans within 4 weeks of commencing and 8 weeks following conventionally‐fractionated concurrent platinum‐based chemoradiation (60 Gy). Intra‐lesional hypoxic volumes of the primary and nodal masses were compared with FDG‐PET metabolic volumes. Baseline tumoural hypoxia was correlated with disease free survival (DFS). Results Seventeen patients underwent pre‐treatment 18F‐FAZA PET and FDG‐PET scans. Intra‐lesional hypoxia was identified on 11 scans (65%). Baseline lesional hypoxic volumes were consistently smaller than FDG‐PET volumes (P = 0.012). There was no statistical difference between the mean FDG‐PET volumes in patients with or without baseline hypoxia (P = 0.38). Eight patients with baseline hypoxia had post treatment 18F‐FAZA scans and 6 of these (75%) had resolution of imageable hypoxia following chemoradiation. The DFS was not significantly different between the hypoxic or non‐hypoxic groups (median 0.8 years and 1.3 years respectively, P = 0.42). Conclusions Intra‐lesional hypoxia, as detected by 18F‐FAZA PET, was present in 65% of patients with locally‐advanced NSCLC and resolved in the majority of patients following chemoradiation. Larger studies are required to evaluate the prognostic significance of the presence and resolution of hypoxia assessed by PET in NSCLC.